1997
DOI: 10.1200/jco.1997.15.10.3266
|View full text |Cite
|
Sign up to set email alerts
|

IDEC-C2B8: results of a phase I multiple-dose trial in patients with relapsed non-Hodgkin's lymphoma.

Abstract: IDEC-C2B8 chimeric anti-CD20 mAb therapy is well tolerated and has clinical activity in patients with relapsed B-cell lymphoma. The 375-mg/m2 dose has been selected for a phase II trial in patients with relapsed low-grade or follicular B-cell lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
314
5
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 577 publications
(340 citation statements)
references
References 18 publications
18
314
5
3
Order By: Relevance
“…After rituximab administration, B lymphocyte depletion in patients occurs rapidly (within days) in the peripheral blood (17). Animal studies have shown that depletion of B cells in lymphoid tissue is rapid and unlikely to continue beyond 2 weeks (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After rituximab administration, B lymphocyte depletion in patients occurs rapidly (within days) in the peripheral blood (17). Animal studies have shown that depletion of B cells in lymphoid tissue is rapid and unlikely to continue beyond 2 weeks (16).…”
Section: Discussionmentioning
confidence: 99%
“…Selective B lymphocyte depletion has been made possible by the availability of the chimeric anti-CD20 monoclonal antibody rituximab (16)(17)(18)(19)(20)(21). CD20 is a B lymphocyte-restricted antigen that is expressed on B lymphocyte precursors and mature B lymphocytes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several Ab have been developed and some of them are currently used in the treatment of patients with hematological malignancies and solid tumors [9]. Rituximab is the most extensively studied chimeric Ab and has been used for the treatment of lowgrade/follicular non-Hodgkin's lymphomas as a single therapeutic agent with a success rate of about 50% [10]. This mouse-human chimeric Ab is directed against CD20 expressed on mature B lymphocytes and on 90% of B cell non-Hodgkin's lymphomas and contains the complement -fixing human IgG1 and j regions [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic administration of such monoclonal antibodies as trastuzumab, cetuximab, and rituximab targeting various proteins on the tumor cell membrane has brought about a milestone in the treatment of certain malignant diseases [4,5]. Although of high therapeutic efficacy, the passive antibody administration suffers from some drawbacks including the need of frequent administration of the drug in varying, but usually rather short time intervals, the necessity for a prolonged duration of drug delivery and the impossibility of application in a prophylactic manner in high-risk patients.…”
Section: Introductionmentioning
confidence: 99%